Treatment of Buccal Lymph-hemangioma by Suction and Intralesional Steroid Injection - Wardhana, Aditya; Sudjatmiko, Gentur; Tiza, Melina (Lingkar Studi Bedah Plastik Foundation, 2012)
Lymphangioma is a tumor-like lesion of lymphatics that most often located in the head and neck area, usually causing marked cosmetic and functional problems. Challenge continues to find a safe and effective modality of treatment for anatomical and functional purposes. Until now, no satisfactory methods in lymphangioma elimination. A 12 years old boy with lymphangioma of the left buccal was referred to the division of Plastic and Reconstructive Surgery in Cipto Mangunkusumo hospital. Suction and intralesional steroid injection was decided as a treatment in this patient. Pressure garment customized the size was made and applied to maintain and prevent healing in sagging position.Long term result should be evaluated, in this patient since the repair just only for 5 months. At follow up, 5 months post operatively after Suction and intralesional steroid injection, the buccal had improved significantly with normal anatomical and functional result. In our experience, the correction of the buccal lymph-hemangioma with suction and intralesional steroid injection was achieved a satisfactory result.